QT INTERVAL CHANGES AT HIGH ALTITUDE: A NARRATIVE REVIEW OF CARDIOVASCULAR RISK AND THE ROLE OF WEARABLE TECHNOLOGIES IN REMOTE MONITORING - Apanasewicz, Katarzyna; Kamrowska , Marta; Świech, Jakub; Kopacki, Filip; Szczeblewska, Weronika; Jaskot, Daniel; Marzec, Jakub; Kita , Natalia; Sztenc, Natalia; Broniszewska, Patrycja (International Journal of Innovative Technologies in Social Science, 2026)
High-altitude exposure induces a range of cardiovascular and electrophysiological adaptations driven primarily by hypobaric hypoxia, autonomic imbalance, and changes in pulmonary hemodynamics. Among these adaptations, alterations in ventricular repolarization, including prolongation of the QT interval and corrected QT (QTc), have attracted increasing attention because of their potential association with arrhythmic risk in both healthy individuals and vulnerable populations. Previous studies have described electrocardiographic changes at altitude, and more recent evidence indicates that QTc may increase during acute or short-term high-altitude exposure and in selected clinical groups, such as patients with obstructive sleep apnea or high-altitude pulmonary hypertension.This narrative review synthesizes current evidence on QT interval changes at high altitude, assesses their potential clinical significance, and evaluates the emerging role of wearable technologies in remote cardiac monitoring under extreme environmental conditions. A structured literature search was conducted using major databases, including PubMed/MEDLINE, Scopus, and Web of Science.The available evidence suggests that high altitude may contribute to measurable changes in ventricular repolarization, although the magnitude, persistence, and clinical implications of these alterations remain heterogeneous across studies. Wearable and smartwatch-based ECG technologies offer promising opportunities for remote surveillance; however, current evidence indicates that QT assessment with such devices still requires careful validation and expert interpretation.These findings may be relevant for clinicians, travelers, and healthcare systems seeking safer strategies for cardiovascular risk assessment in remote and high-altitude environments.